The Effectiveness of Using Duolingo Application for Speaking Skill in 10th Grade of SMK Pariwisata Budaya Bedulu - Pande Kadek Adyta; Ni Putu Ratni; Ni Wayan Satri Adnyani (Indo Publishing, 2026)
This study examined the effectiveness of the Duolingo application in improving the speaking skills of tenth-grade students at SMK Pariwisata Budaya Bedulu. The study used a quasi-experimental design involving an experimental group taught using Duolingo and a control group taught using conventional media. The participants consisted of 66 students divided into two classes. Data were collected through pre-test and post-test speaking assessments covering pronunciation, fluency, vocabulary, grammar, and comprehension. The findings showed that the experimental group improved from a mean score of 52.73 to 75.30, while the control group improved from 51.36 to 72.42. However, the Mann-Whitney U test showed a significance value of 0.238, which was higher than 0.05. Therefore, statistically there was no significant difference between the two groups, although the experimental group showed better improvement descriptively. These findings are related to Cognitive Learning Theory, which emphasizes practice and active learning. The study concludes that Duolingo can support students’ speaking skills as a digital learning medium.